Chileotrecha romero (Kraus, 1966) comb. nov. and Pseudocleobis patagonicus (Roewer, 1934) comb. nov. transferral from Mummuciidae to Ammotrechidae (Arachnida, Solifugae) - Botero-Trujillo, Ricardo; Iuri, Hernán A. (Zootaxa, 2015)
The solifuge species Mummucina romero Kraus, 1966, from Chile, and Mummucia patagonica Roewer, 1934, from Argentina, are here transferred from Mummuciidae Roewer, 1934 to Ammotrechidae Roewer, 1934. Chileotrecha romero (Kraus, 1966) comb. nov. and Pseudocleobis patagonicus (Roewer, 1934) comb. nov. are proposed. Comments on their morphology are made and previous distributional records are discussed. Pseudocleobis patagonicus is proposed as a nomen dubium. In addition, we confirm that female and immature specimens of the family Mummuciidae, just like males, can be reliably recognized based on features that had been suggested by Maury (1984).